Global research trends on the associations between the microbiota and lung cancer: a visualization bibliometric analysis (2008–2023) - Zhao, Maoyuan; Tian, Jie; Hou, Wang; Yin, Liyuan; Li, Weimin (Frontiers in Microbiology, 2024)
Numerous papers have been published on the microbiota in lung cancer in recent years.However, there is still a lack of bibliometric analysis of the microbiota in lung cancer in this field. Our paper did bibliometric analyses and elucidated the knowledge structure and study hotspots related to the microbiota in lung cancer patients. We screened publications reporting on the microbiota in lung cancer from 2008 to 2023 from the Web of Science Core Collection (WoSCC) database, and carried out bibliometric analyses by the application of the VOSviewers, CiteSpace and R package "bibliometrix". The 684 documents enrolled in the analysis were obtained from 331 institutions in 67 regions by 4,661 authors and were recorded in 340 journals. Annual papers are growing rapidly, and the countries of China, the United States and Italy are contributing the most to this area of research. Zhejiang University is the main research organization. Science and Cancer had significant impacts on this area.Zhang Yan had the most articles, and the Bertrand Routy had the most co-cited times.Exploring the mechanism of action of the lung and/or gut microbiota in lung cancer and therapeutic strategies involving immune checkpoint inhibitors in lung cancer are the main topics. Moreover, "gut microbiota", "immunotherapy" and "short-chain fatty acids" are important keywords for upcoming study hotspots. In conclusion, microbiota research offers promising opportunities in lung cancer, with pivotal studies exploring the mechanisms that link lung and gut microbiota to therapeutic strategies, particularly through immune checkpoint inhibitors. Moreover, the gut-lung axis emerges as a novel target for innovative treatments. Further research is essential to unravel the detailed mechanisms of this connection.